Determinants of Youth Motivation in Agricultural Careers: A Systematic Review for Regeneration Strategy Formulation in Indonesia - Juniasih, Ida Ayu Komang; Wibawa, Made Satria; Suastama, Ida Bagus Radendra; Nona, Reyna Virginia; MERUNG, ARTEURT YOSEPH (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 19 No 1 (2025), 2025)
The agricultural sector in Indonesia faces serious challenges regarding the low interest and participation of the younger generation. This study aims to conduct a comprehensive systematic literature review to identify the key determinants or factors influencing farming motivation among Indonesian youth. This qualitative research employed a systematic and structured literature review approach by conducting an in-depth search through reputable journal databases. The review findings reveal negative perceptions of farming as a profession, low income and welfare among farmers, and inadequate infrastructure and institutional support are significant barriers to attracting youth interest. Thematic analysis identified 16 key factors motivating Indonesian youth to engage in farming: government support, creativity, family support, technology, social environment, mindset, training, extension services, digital communication, digital education, environmental awareness, formal education, cosmopolitanism, infrastructure availability, adoption and innovation, and community involvement. The policy implications emphasize strengthening technology-based training programs and financial incentives to address these challenges.